THE EFFECT OF FINANCIAL LITERACY AND PERSONALITY TOWARDS STUDENTS’ FINANCIAL MANAGEMENT ABILITY - Nur Fitrah Ramadhani Liesfi; Suranto Suranto (Assets: Jurnal Akuntansi dan Pendidikan, 2021)
ABSTRACTThis study aims to find out the effect of financial literacy and personality traits on personal financial management. The population in this study was all students of the Faculty of Economics, which consisted of 1068 students, and 258 students were selected as the samples of this study using a proportional cluster random sampling system. The data analysis technique used was multiple linear regression. The result of this study showed that financial literacy and personality, whether simultaneous or partial, significantly and positively affect the personal financial management of students.ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh literasi keuangan dan ciri-ciri kepribadian terhadap pengelolaan keuangan pribadi. Populasi dalam penelitian ini adalah seluruh mahasiswa Fakultas Ekonomi yang berjumlah 1068 mahasiswa dan dipilih sebanyak 258 mahasiswa yang digunakan sebagai sampel dalam penelitian ini dengan menggunakan teknik proportional cluster random sampling. Teknik analisis data yang digunakan adalah regresi linear berganda. Hasil dari penelitian ini menunjukkan literasi keuangan dan kepribadian, baik secara simultan ataupun parsial, berpengaruh positif dan signifikan terhadap pengelolaan keuangan pribadi mahasiswa.